Frontiers in Stem Cell and Regenerative Medicine Research: Volume 11 - Anjum, Shazia (Bentham Science Publishers, 2024)
Stem cell and regenerative medicine research is an important area of clinical research which promises to change the face of medicine as it will be practiced in the years to come. Challenges in the 21st century to combat diseases such as cancer, Alzheimer's disease and retinal disorders, among others, may well be addressed employing stem cell therapies and tissue regeneration techniques. Frontiers in Stem Cell and Regenerative Medicine Research brings updates on multidisciplinary topics relevant to stem cell research and their application in regenerative medicine. The series is essential reading for researchers seeking updates in stem cell therapeutics and regenerative medicine.Volume 11 includes 5 chapters on these topics:- The use of embryology in clinical practice- Molecular regulation and signaling transduction in human tissue development- Cell differentiation on hydrogels and its application in regenerative medicine- Stem cell therapy for sepsis- Tumorigenicity assessments for stem cell-derived therapeutic products.